Sustainable preparation of metal nanoparticles : methods and applications - Luque, Rafael; Varma, Rajender S. (RSC green chemistry series, 2013)
"This timely publication bridges and presents the latest trends and updates in three hot topics of current and future society: nanomaterials, energy and environment. It provides the state-of-the-art as well as current challenges and advances in the sustainable preparation of metal nanoparticles and their applications. The book fills a critical gap in a multidisciplinary area of high economic, social and environmental importance. Currently, there are no books published that deal with these ever increasing important topics, as most books in this area focus on a particular topic (eg. nanomaterials or catalysis or energy or environment). This is the first multidisciplinary edited book covering the very basics to the more advanced, trendy developments, containing a unique blend of nano, green, renewable and bio"--Provided by publisher.